Kinetics of VO2 in professional cyclists - Lucia, A.; Hoyos, J.; Santalla, A.; Perez, M.; Chicharro, J. L. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: To analyze the kinetics of oxygen uptake (VO2) in professional road cyclists during a ramp cycle ergometer test and to compare the results with those derived from well-trained amateur cyclists. METHODS: Twelve professional cyclists (P group; 25 +/- 1 yr; maximal power output (Wmax), 508.3 +/- 9.3 watts) and 10 amateur cyclists (A group; 22 +/- 1 y; Wmax, 429.9 +/- 8.6 watts) performed a ramp test until exhaustion (power output increases of 25 watts.min[minus sign]1). The regression lines of the VO2:power output (W) relationship were calculated for the following three phases: phase I (below the lactate threshold (LT)), phase II (between LT and the respiratory compensation point (RCP)), and phase III (above RCP). RESULTS: In group P, the mean slope ([Delta]VO2:[Delta]W) of the VO2:W relationship decreased significantly (P < 0.01) across the three phases (9.9 +/- 0.1, 8.9 +/- 0.2, and 3.8 +/- 0.6 mL O2.watts[minus sign]1. min[minus sign]1 for phases I, II, and III, respectively). No significant differences (P > 0.05) were found between phases I and II (P > 0.05) in group A, whereas [Delta]VO2:[Delta]W significantly increased in phase III (P < 0.01), compared with phase II (10.2 +/- 0.3, 9.2 +/- 0.4, and 10.1 +/- 1.1 mL O2.watts[minus sign]1. min[minus sign]1 in phases I, II, and III, respectively). The mean value of [Delta]VO2:[Delta]W for phase III was significantly lower in group P than in group A (P < 0.01). CONCLUSION: Contrary to the case in amateur riders, the rise in VO2 in professional cyclists is attenuated at moderate to high workloads. This is possibly an adaptation to the higher demands of their training/competition schedule.